Fly-ash-based geopolymers: leachability and solid-state NMR investigations - Nadol, Athulya; Ajithkumar, T. G.; Singla, Rashmi; Alex, T. C.; Kumar, Sanjay; Bhatt, Himal; Deo, M. N.; Sen, Debasis; Ambashta, R. D.; Bajpai, R. K.; Shivakumar, Y. C.; Manohar, S. (Bulletin of Materials Science, 2026)
This study aims to explore how leaching impacts the microstructure of a selected fly ash-derived geopolymer and evaluate its potential for near-surface disposal of radioactive waste. The uniqueness of this geopolymer formulation is its ability to form an aluminosilicate network that remains resistant to structural changes upon contact with water. The leach index of base elements such as Ca, Al, Na and Si was between 11 and 13, suggesting that the formulation is superior to Portland cement or conventional hydraulic cement. Solid-state NMR reveals that the water-interacted specimen has no contamination of the zeolite phase and all the Na is incorporated into the aluminosilicate geopolymer gel network, which also confirms that the glassy network of the geopolymer is responsible for imparting low leachability of base elements from its structure, and there is no labile sodium available for exchange as in zeolites.
Keywords: aluminosilicate network; Fly ash; Geopolymers; leaching; Solid-state NMR